Algunas notas sobre el exorcismo en el occidente latino en la Antigüedad Tardía - López Campuzano, Manuel; González Fernández, Rafael (Antigüedad y Cristianismo, 1991)
The purpose of this article is the presentation of information about Exorcism in I he western world during the late antiquity, from the point of view historical - antropological, and based on the ancient clasical authors, especially on the hagiographies. These demostrate the power of the holy man trying to cure the evil which afflicts his social surroundings by means of the exorcism, trying to reintergrate the possesed individual once again into the community using a type of public confession, probably based on the Roman Juridical model.